Signatures of quantum gravity - Iyer, AV (2022)
This thesis discusses the hurdles that are frequently encountered in attempts to quantize gravity or rather, while gravitizing quantum mechanics. Among the issues we consider here are the lack of observable signatures of the quantum nature of gravity despite the considerable amount of effort directed towards theoretical approaches such as string theory and loop quantum gravity, to name a few. Here, we examine observable consequences of quantum gravity through superpositions of primordial massive particles and quantum witnesses in table top experiments involving Bose Einstein Condensates. We compute the decoherence timescales of a primordial superposition and outline its effects in the form of an interference pattern, characteristic absorption spectra or entanglement effects. While it is difficult to conceive of a way to control measurements that occur in the early universe, such as the measurement of curvature perturbations during inflation, we have a significant degree of control over quantum systems in the laboratory such as Bose Einstein Condensates for which we propose a non-Gaussianity based witness of the quantum nature of gravity. Non-Gaussianities are also discussed in the context of cosmological observations where it becomes important to distinguish primoridal non-Gaussianities from secondary effects. While observing any of these signatures can give credence to the requirement that gravity should be quantum, insight can also be drawn between conflicts that exist between general relativity and quantum mechanics. One such anomaly we discuss is the cosmic censorship conjecture and its reconciliation with quantum information theory. In particular by employing the complexity-volume conjecture from the AdS/CFT correspondence, we show that for Kerr black holes, spacetime must continue across the Cauchy Horizon where solutions to the Einstein field equations break down. Finally, we introduce a formalism that attempts to bridge the gap between quantum theory and relativity by putting spacelike and timelike events on the same footing. The notion of an event, redefined as a correspondence between a system and an apparatus, gives rise to interesting predictive phenomena and allows us to apply the tools of quantum information theory in their characterisation.